2019
DOI: 10.1111/cga.12339
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular swelling in the cervical region with lymph sac formation in human embryos

Abstract: Vesicular swelling in the cervical region (VSC) is occasionally observed among human embryos around Carnegie stage (CS) 21. However, its mechanism and significance in fetal development are unclear. The present study aimed to analyze the relation of development of VSC with jugular lymph sac (JLS) formation. Serial histological sections that were digitalized from 14 embryos at CS20 and CS21 stored at the Kyoto Collection were used for the analysis. Subcutaneous edema and enlargement of the subarachnoid space wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(58 reference statements)
0
0
1
Order By: Relevance
“…The left JLS (2.53 mm 3 ) was larger than the right JLS (1.93 mm 3 ). These results indicated that our results were slightly different than those of Carnegie stages 20 and 21 [10] .…”
Section: Discussioncontrasting
confidence: 81%
“…The left JLS (2.53 mm 3 ) was larger than the right JLS (1.93 mm 3 ). These results indicated that our results were slightly different than those of Carnegie stages 20 and 21 [10] .…”
Section: Discussioncontrasting
confidence: 81%
“…[ 3 - 10 ] The most widely accepted theories to explain the NT increase are cardiac dysfunction/failure or venous congestion in the fetal head and neck,[ 9 ] alterations in extracellular matrix components,[ 10 ] conditions such as fetal anemia, infection, and hypoproteinemia,[ 11 ] and disorders of lymphangiogenesis. [ 12 ] However, these theories could not explain the reason for the localization of such thickening to the neck of the fetus or the transient nature of this finding. It has also remained unexplained why concomitant EJLS appeared simultaneously in some cases and not in others.…”
Section: Introductionmentioning
confidence: 98%